Mental Imagery Skills in Alcohol-Dependent Subjects and Their Associations With Cognitive Performance: An Exploratory Study During Residential Rehabilitation - Ottonello, Marcella; Torselli, Elisa; Caneva, Stefano; Fiabane, Elena; Vassallo, Claudio; Pistarini, Caterina (Frontiers in Psychiatry, 2021)
People in alcohol-detoxification experience deficits in motor and nonmotor functions including cognitive performance. Imagery, the cognitive process of generating visual, auditory or kinesthetic experiences in the mind without the presence of external stimuli, has been little studied in Alcohol Use Disorders. This pilot study aims to observe the cognitive abilities useful for the inspection, maintenance, generation and manipulation of images in these patients during residential rehabilitation and investigate the relationships with their cognitive performance. Thirty-six subjects who completed the 28-day rehabilitation program for alcohol addiction, completed the Mental Imagery Test (MIT) and Neuropsychological Battery (ENB-2). The global score at MIT did not show pathological scores. The 11.1% of AUD patients showed an impaired global score in the cognitive performance and the 5.7% with scoring at limits of norm. Significant correlations were found between Mental Imagery abilities and ENB-2 subscale and stepwise regression analysis showed the ability of imagery (Mental Imagery Test) to predict the overall cognitive performance (ENB-2) in alcohol dependent patients and this prediction is higher than other cognitive tasks.